Assessment of student learning outcomes in engineering education and impact in teaching - Alfredo Soeiro (2013)
It is presented a conceptual model that aligns Learning Outcomes (LO) in Engineering Education (EE) with assessment strategies based on e-learning. The research problem was made taking into account three areas of research: Assessment, Engineering Education and e-Learning. The work managed to verify to what extent e-assessment methods may be used to measure intended Learning Outcomes of Engineering courses. The study was planned to facilitate the curriculum design, the teaching delivery planning, the recognition of e-learning courses and to improve definition of assessment tools. In general terms, the approach chosen was to develop a model that matches various common assessment methods to measure the achievement of the main Learning Outcomes (LO) in the field of engineering. This means that it should be possible for a teacher to define the intended LO of the engineering course and, considering this definition, to write proper and possible adequate assessment methods. The work done in the study proposes a conceptual model ALOE (Assessment of Learning Outcomes in Engineering). ALOE was used to describe the Learning Outcomes and the proper assessment and to achieve alignment between these two components of the educational process. The impact in teaching that resulted from the application of ALOE is evaluated based in some case studies. The impact is presented in terms of curriculum organization, assessment methods, teaching activities and learning evaluation results.